Pengaruh Aplikasi Dolomit terhadap Mutu Benih Jagung (Zea mays L.) pada Tanah Masam di Kebun Percobaan Fakultas Pertanian Universitas Udayana - ALPREDO CHRISTIAN STOMPUL; NI LUH MADE PRADNYAWATHI; NI NYOMAN ARI MAYADEWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Effect of Dolomite Application on the Quality of Corn Seeds (Zea mays L.) on Acid Soil in Experimental Gardens, Faculty of Agriculture, Udayana University The decline in maize production in Bali is caused by various factors such as poor cultivation techniques, lack of agricultural land due to land conversion, limited fertile land due to acidic soil conditions and the availability of quality seeds that are still lacking. The application of dolomite on acid soil is expected to improve the quality of corn seeds. This study aims to determine the difference in the effect of dolomite application and without dolomite application on acid soil on corn seed quality (physical and physiological quality). This study used a paired experiment to compare the quality of corn seeds produced with dolomite application and without dolomite application. The results showed that the application of dolomite was able to significantly increase the average weight of 1000 seeds, germination, shelf life vigor, growth speed vigor of 2.55%, 1.23%, 6.27%, 3.43 % when compared with no dolomite application, while the simultaneous growth of vigor showed no significant difference between dolomite application and without dolomite application.